Biliary protozoa in a dog with acute cholangiohepatitis fed a raw food diet. (30th September 2022) - Allan, Frederik; Blake, Damer; Miller, Zoe; Church, David
Abstract: A 1‐year 11‐month intact female Alaskan Malamute fed a raw food diet was referred to the Queen Mother Hospital for Animals for further investigation of hyporexia and increased hepatobiliary enzyme activities. Clinicopathological and imaging findings were consistent with cholangiohepatitis, with coccidial zoites identified on bile cytology. Polymerase chain reaction and amplicon sequencing from the bile identified Hammondia heydorni, a Sarcocytid coccidial protozoa with an obligate 2‐host life cycle. The dog was treated with clindamycin, marbofloxacin, ursodeoxycholic acid (UDCA) and S‐adenosylmethionine/silybin with complete clinical and biochemical resolution documented after 6 weeks. Infection with Hammondia spp. should be considered in patients receiving raw food diets in which coccidial zoites are identified in the bile, but the pathogenic potential of this organism is unknown and the possibility of its presence as a commensal cannot be discounted.